Estimating Value Added Tax Gap in Uzbekistan - I. M. Niyazmetov (Финансы: теория и практика)
The subject of the paper is to study of the theoretical literature on evaluate the effectiveness of the value added tax (VAT) mechanism, and identification of criteria for the analysis of the VAT mechanism. The purpose of the paper is to investigate methods for evaluating the effectiveness of VAT mechanism and, on that basis, to evaluate the VAT gap in Uzbekistan and the factors influencing it. The importance of the paper is confirmed by the significant contribution of the tax to the sufficiency and stability of budget revenue in countries with consumption tax mechanisms. A mathematical approach based on the C-efficiency (Collection efficiency) ratio is used to calculate the VAT gap. This model evaluates the discrepancy between actual VAT income and the maximum amount of tax revenue that could be obtained by taxing all (and only) final consumer spending in the economy. The novelty of the paper is justified by adaptation of model to the specification of VAT structure of Uzbekistan and recent data to estimate VAT gap. The research concluded that Uzbekistan’s VAT mechanism is twice as inefficient as its ideal mechanism. Estimates for 2016 and 2020 indicate that on average a quarter of potential VAT revenue is not collected due to Compliance Gap, while Policy Gap is responsible for over a third of the ideal loss of VAT revenue. In order to improve compliance, it is recommended to optimize the collection and control systems in addition to policy modifications that include reforms of tax objects, subjects, rates, incentives, and other tax elements.